Effective Department Meetings: The right approach varies - Deborah S Richardson; Richard Griner; Angela Morgan; James Burgess (Academic Chairpersons Conference Proceedings, 2019)
This workshop will provide positive and instrumental approaches to meeting planning and management that allow chairs to effectively address challenging situations with confidence. Scenarios where specific meeting dynamics may be implemented to address difficult situations or maximize productivity will be discussed in breakout groups and finally considered by all.
Keywords: Meeting Planning; faculty challenges; managing meeting dynamics; productive meetings; efficient meetings